Effect of Non-Debt Tax Shield, Growth, Size, and Asset Structure of Firm Value and Capital Structure - Lia Rachmawati (KUNKUN: Journal of Multidisciplinary Research, 2024)
This study aims to analyze the effect of non-debt tax shield, growth, size, and asset structure on firm value with capital structure as an intervening variable in coal sub-sector mining companies listed on the Indonesia Stock Exchange in 2014-2018. The data used in this research is secondary data. The sample selection in this study was carried out by purposive sampling. Based on the existing criteria, a sample of 15 companies was obtained. The data analysis technique used is path analysis. Based on data analysis of the four independent variables, only the non-debt tax shield variable and size have a significant effect on capital structure, and of the four independent variables only size has a significant effect on firm value. The independent variable is able to moderate the non-debt tax shield, growth, and size capital structure variables, while the asset structure variable is not able to moderate the capital structure to firm value